Multi-institutional Analysis of 100 Consecutive Patients with COVID-19 and Severe Pulmonary Compromise Treated with Extracorporeal Membrane Oxygenation: Outcomes and Trends Over Time. Issue 5 (May 2021) - Jacobs, Jeffrey p.; Stammers, Alfred H.; Louis, James St.; Hayanga, J.W. Awori; Firstenberg, Michael S.; Mongero, Linda B.; Tesdahl, Eric A.; Rajagopal, Keshava; Cheema, Faisal H.; Patel, Kirti; Esseghir, Feriel; Coley, Tom; et al.
Abstract : The role of extracorporeal membrane oxygenation (ECMO) in the management of severely ill patients with coronavirus disease 2019 (COVID-19) continues to evolve. The purpose of this study is to review a multi-institutional clinical experience in 100 consecutive patients, at 20 hospitals, with confirmed COVID-19 supported with ECMO. This analysis includes our first 100 patients with complete data who had confirmed COVID-19 and were supported with ECMO. The first patient in the cohort was placed on ECMO on March 17, 2020. Differences by the mortality group were assessed using χ 2 tests for categorical variables and Kruskal–Wallis rank-sum tests and Welch's analysis of variance for continuous variables. The median time on ECMO was 12.0 days (IQR = 8–22 days). All 100 patients have since been separated from ECMO: 50 patients survived and 50 patients died. The rate of survival with veno-venous ECMO was 49 of 96 patients (51%), whereas that with veno-arterial ECMO was 1 of 4 patients (25%). Of 50 survivors, 49 have been discharged from the hospital and 1 remains hospitalized at the ECMO-providing hospital. Survivors were generally younger, with a lower median age (47 versus 56.5 years, p = 0.014). In the 50 surviving patients, adjunctive therapies while on ECMO included intravenous steroids (26), anti-interleukin-6 receptor blockers (26), convalescent plasma (22), remdesivir (21), hydroxychloroquine (20), and prostaglandin (15). Extracorporeal membrane oxygenation may facilitate salvage and survival of selected critically ill patients with COVID-19. Survivors tend to be younger. Substantial variation exists in the drug treatment of COVID-19, but ECMO offers a reasonable rescue strategy.